Simulations of long-term anaerobic corrosion of carbon steel containers in Canadian deep geological repository. (September 2014) - King, F.; Kolář, M.; Keech, P. G.
<x content-type="archive" xml:space="preserve">Abstract</x> Carbon steel is a candidate container material for the disposal of used fuel in a deep geological repository in sedimentary host rock in Canada. Prediction of the long term anaerobic corrosion behaviour of the container is important, not only because it partly determines the container lifetime but also because the products of the corrosion reaction, Fe(II) and H2, can impact the properties of the clay based sealing materials and host rock. A mechanistically based numerical model is described that predicts both the long term corrosion rate and the effects on the repository environment, including the periodic build-up and release of H2, the precipitation of Fe3O4 within the bentonite buffer, and the alteration of montmorillonite to a non-swelling clay. The results of a reference simulation for a repository in shale host rock are described.